NANOEMULSION CHARACTERISTICS PREPARATIONS ETHANOL LEAF EXTRACTS IN VARIOUS PLANTS: LITERATURE REVIEW - Nora Nur Aini; Ratna Wijayatri; Prasojo Pribadi (Universitas Muhammadiyah Magelang, 2022)
Nanoemulsion is one of the nanotechnology applications that can measure particles 0-100 nm which has control of the release of active ingredients and good sensory properties. Nanoemulsion of ethanol leaf extract in various plants has considerable potential in the utilization of natural materials. The solvent used is an important factor. This research focuses on plant leaf parts with ethanol extract. The purpose of this review is to study, evaluate and analyze literature focused on the characteristics of nanoemulsion preparations of ethanol leaf extracts in various plants related to nanoemulsion components, manufacturing methods, and nanoemulsion preparation characteristics. This research uses the method of literature review or narrative review, the search for published scientific literature is indexed in various databases. Search articles through various databases to ensure that the majority of relevant studies have been identified. Based on the results of the literature review concluded that the most widely used surfactant in the review of these articles is Polysorbat 80 or Tween 80 which is a non-ionic and non-irritative surfactant commonly used in pharmaceutical and cosmetic preparations. Ultrasonification and microfluidation methods are also applied in some articles because they are capable of producing a minimum droplet diameter of 150 to 170 nm..The results of the study of particle size in the article produced particle sizes between 10.9 nm-312.1 nm. Indeks polidispersitas value 0.08-0.7 zeta potential value above +/-30 and EE value shows value above 80%. It can be concluded that the nanoemulsion characteristics of each article meet the requirements and produce stable nanoemulsions.